The establishment and operation of the first modern prison during the First Republic of Poland (1767-1795) - Jerzy Czołgoszewski (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Modern prison service in the First Republic of Poland began to take shape in terms of organization with the establishment in Warsaw, the capital of the Republic and the development of the judiciary, especially judicial marshal. The reforms giving rise to the modern penitentiary system were undertaken in 1766. After taking office Grand Marshal of the Crown by Prince Stanislaw Lubomirski, on whose initiative began operating the first prison, known from the earlier the purpose as "Prochownia". The article presents a very progressive, compared to other working earlier and present prisons, prison system. Discussed destiny of prison, sources of financing its activities and the established order of the day. In addition, a characteristic change in the treatment of prisoners, the introduction of a wide system of employing prisoners, disciplinary responsibility and aid to prisoners redundant were also fully analyzed. The period of time the prison system of the First Republic ended the third partition of Poland.